How Incorporating Deliberate Practice in Work Placement May Contribute to Developing Expertise in Translators - Sadza, Agata (Research in Language, 2021)
The article explores some of the ways in which work placement that accompanies or follows academic instruction may contribute to stimulating trainee translators’ professional development. Inspired by general and profession-specific concepts and components of expertise proposed by researchers in the field of cognitive sciences and translation studies as well as her own experience as a translator, translation trainer, and work placement mentor, the author presents some of her observations and preliminary highlights of her ongoing research to emphasise how individualised support for trainees’ conscious effort in the course of work placement in a translation company may help novice translators hone their skills and at the same time assume responsibility for their own development, thus empowering them and setting them on track to become experts. In her considerations, the author refers to the minimal concept of translation expertise propounded by Muñoz Martín (2014) and to the notion of deliberate practice as posited by Ericsson et al. (1993) to propose how deliberate practice may be implemented as one of the significant elements of translation work placement in a student-centred course of learning, where various aspects of the actual workplace setting contribute to increased readiness for conscious effort in trainees. This paper may prove of use to translator trainers as well as work placement mentors/coordinators, both on the part of the academic institution, and within the organisation accepting trainees, when they shape or revise their curricula or work placement agendas.